Cold contact: a study of Canada-US relations in the Arctic - Hamm, Nicole (2010)
Since the end of World War II, through the mandates of Prime Ministers Pierre Trudeau, Brian Mulroney, Jean Chrétien, Paul Martin and Stephen Harper, the Canadian government has found itself in conflict with the US Administration over the question of Arctic sovereignty. This situation is particularly difficult because of the power imbalance between the two countries. Thus, how Canada deals with the US is critical. John Kirton identifies five ways in which Canada manages its differences with the US on foreign policy issues. The first is the process of ad hoc adjustment and problem-solving on individual issues. A second way is by pursuing solutions that achieve integration and cooperation. The third strategy consists of building defences and taking initiatives to reduce Canada’s vulnerability to the US. The fourth strategy involves the deliberate influencing of the US domestic policy process in order to create policy that is more advantageous to Canadians. In the fifth strategy, Canada aligns itself with others in the international community, building coalitions that can match the power and strength of the US; but more importantly, it establishes a place for Canada to lead the discussion and pursue its own interests. John Holmes believed that Canadian foreign policy was best served by multilateralism, as Canada often found it difficult to further its own interests within a bilateral framework. Kirton takes Holmes’ argument one step further by observing that by playing a leadership role in the multilateral arena on specific issues, Canada can help find global solutions that advance Canadian interests. This thesis uses Kirton’s analytical framework to examine the strategies that Canada has employed in dealing with conflicts with the US over the Arctic. It examines the Trudeau, Mulroney, Chrétien, Martin and Harper governments and finds a common thread in their approaches. While showing that each one adopted a number of the strategies identified by Kirton, the thesis draws particular attention to their common ...